Oscillatory Effect on Magneto - Hydrodynamic Flow and Heat Transfer in a Rotating Horizontal Porous Channel: Investigation of the Effects of Magnetic Fields on Oscillatory Flow and Heat Transfer in a Rotating Porous Channel (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present paper studies the effects of injectionsuction on an oscillatory flow of a viscous incompressible fluid in a porous channel under the influence of a magnetic field acting normally to the plates of channel. The Channel with variable temperature and constant injectionsuction rotates about an axis perpendicular to the plates of channel. The upper plate of the channel is allowed to oscillate in its own plane whereas the lower plate is held at rest. The heat transfer is analyzed under two conditions, the temperature of upper plate of channel starts oscillations whereas the temperature of lower plate is kept fixed. It is interesting to note the magnetic fields fixed relative to the moving plate contribute more to the resultant velocity than the magnetic field fixed relative to the fluid. Another striking result is that the frequency of oscillation has a distinct effect when the magnetic field is fixed relative to fluid. The effect of all pertinent parameters on phase angle is just opposites to that of resultant velocity owing to the relative position of magnetic fields.